2010
DOI: 10.1063/1.3532851
|View full text |Cite
|
Sign up to set email alerts
|

Secondary electron yield of multiwalled carbon nanotubes

Abstract: Extension-induced dispersion of multi-walled carbon nanotube in non-Newtonian fluidSecondary electron yield from individual multiwalled carbon nanotubes is investigated for a wide range of primary beam energies ͑0.5-15 keV͒. By using a simple experimental procedure under an optical microscope, we make suspended nanotubes, which are free from interaction with the substrate during electron yield measurements. It is found that the secondary electron yield from isolated suspended nanotubes is less than unity and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Thence by multiplying this increase by the ratio of the length of the scanned area over the SWNT diameter, they deduced that SWNTs connected to a reservoir have a secondary electron emission coefficient ͑SEEC͒ of up to 123, far higher than expected based on existing reports on the interaction of electron beams with carbon nanotubes ͑CNTs͒ and their scanning electron microscopy. [2][3][4][5][6][7][8][9] The analysis presented by the authors of Ref. 1 does not take into account the effect of the SiO 2 film underneath the CNTs adequately.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thence by multiplying this increase by the ratio of the length of the scanned area over the SWNT diameter, they deduced that SWNTs connected to a reservoir have a secondary electron emission coefficient ͑SEEC͒ of up to 123, far higher than expected based on existing reports on the interaction of electron beams with carbon nanotubes ͑CNTs͒ and their scanning electron microscopy. [2][3][4][5][6][7][8][9] The analysis presented by the authors of Ref. 1 does not take into account the effect of the SiO 2 film underneath the CNTs adequately.…”
mentioning
confidence: 99%
“…Ideally one should measure the SE current from a CNT that is freestanding over a region of negligible SEEC where bombarded with electrons. 9 The authors suggested that the claimed high value of SEEC can be explained by the primary electron raising the highest occupied molecular orbital ͑HOMO͒ above the vacuum level. But such a drastic raise of the HOMO applies to the CNT tip in the presence of a strong external electric field.…”
mentioning
confidence: 99%
“…For instance, if the beam spot diameter had been larger than individual nanotube diameters, we would have a higher emitted current -and therefore higher specimen current -when the beam crossed the much-larger-diameter nanotube bundle (near the end of the arrow on Fig. 1(c)(i)) 5 than when it crossed the smaller-diameter individual nanotube (near the beginning of the arrow). This is clearly not the case and the specimen current is essentially the same for all the nanotubes and bundles in the scan (Fig.…”
mentioning
confidence: 99%
“…The comment and Ref. 3 do not give any evidence to falsify our imaging mechanism and the mathematical derivation of Eq. ͑1͒ in our Letter.…”
mentioning
confidence: 99%
“…This should be the concern in the second paragraph of the comment and in the criticism of our work in Ref. 3. In order to explain our SEM images, we have included the SE signal from the SiO 2 in each unit point as a separate term in the imaging mechanism, as shown in Eqs.…”
mentioning
confidence: 99%